Effect of rearing conditions on fatty acid allocation during flight in nectivorous lepidopteran Mythimna unipuncta - Anparasan, Libesha; Hobson, Keith A.; McNeil, Jeremy N. (Frontiers in Ecology and Evolution, 2023)
Insect species that are nectivorous as adults acquire essential fatty acids almost exclusively from host plants during larval development. Thus, as essential fatty acids are important for a number of different biological processes, adult allocation of this limited resource may result in important trade-offs. Most migratory lepidopteran species migrate as sexually immature adults, so essential fatty acids used for migratory flight would not be available for subsequent reproduction. Using the true armyworm, Mythimna unipuncta, as a model system we analysed fat body samples to test the hypothesis that environmental cues would influence the use of essential fatty acids during migratory flight. We used diets manipulated isotopically to trace origins and use of stored lipids and used chromatographic analyses to determine fatty acid composition. In the first experiments, five-day old moths that had been reared in summer or fall (migratory) conditions were force flown for different lengths of time (0-6h) after which samples of the fat body were analysed. Rearing conditions did not affect fatty acid loading, however patterns of use during flight differed with essential fatty acids, being conserved under fall but not summer conditions. As migratory flight can take several days, we repeated the experiment when five-day old moths were flown for 8h each day for up to five days. Some moths were provided access to sugar water after each flight while others were only given water. When sugar water was readily available, moths reared under fall conditions conserved their essential fatty acids while those under summer (non-migratory) conditions did not, indicating that the environmental cues responsible for the onset of migratory flight result in physiological changes that modify lipid use. However, when moths had only water, the essential fatty acids were not conserved, highlighting the importance of nectar availability at stopovers on the conservation essential fatty acids during migration. Isotopic analysis of the moth fat body indicated a large contribution of adult-derived diet to lipids used as fuel. The implications of using isotopic approaches to other flight studies and future research on differential resource allocation in winged monomorphic migratory insects are discussed.